Effect of water-to-cement ratio on sulfo-aluminate type cementitious grouting materials. Issue 6 (3rd June 2018) - Chen, Xuexi; Bi, Ruiqing; Zhang, Liang
Abstract : Aiming to remedy the deficiency of research related to water-to-cement (w/c) ratio (near 1·0) grouting materials, particularly calcium-sulfo-aluminate (CSA)-type cementitious grouting materials, we discuss the influence of w/c ratio on CSA-type cementitious grouting materials. Various experimental data sets reveal that the cube strength, hydration exothermic rate, total energy released and in situ non-destructive resistivity all decrease with increasing w/c ratio. It is observed that pompom spherulites of ettringite differ from most cementitious materials. A lower solution concentration resulted in thicker ettringite crystal prisms. The results also show that these spherulites form because of excessive dehydrate gypsum, which also causes unexpected X-ray diffraction results in the induction period; the content of ettringite of the 1·0-w/c hardened material was highest, whereas that of the 0·8-w/c material was the lowest, indicating that the contact probability among the Al 3+, SO4 2−, and ye'elimite (C4 A3 S̄) crystals that act as nucleation sites becomes low, the ion-dissolution rate of the C4 A3 S̄ framework and the precipitation rate of ettringite both decrease, the Al–O octahedral nucleation barrier increases and the crystal nucleation critical size increases.